Distance to the Efficiency Frontier and FDI Spillovers - Klara Sabirianova Peter; Jan Svejnar; Katherine Terrell (Institute for the Study of Labor (IZA), 2004)
We establish that domestically owned firms in two alternative models of emerging market economies, the Czech Republic and Russia, have not been converging to the technological frontier set by foreign owned firms. In both countries, the distance of domestic firms to the frontier grew (in all parts of the distribution) from 1992-1994 to 1995-1997 and did not change from 1995-1997 to 1998-2000. However, the distance to the frontier is orders of magnitude greater in Russia than in the Czech Republic throughout 1992-2000. We also find in both countries that domestic firms in industries with a greater share of foreign firms are falling behind more than domestic firms in industries with a smaller foreign presence. However, in the Czech Republic this ?negative spillover? effect is diminished over time, whereas in Russia it continues to cause domestic firms to fall further behind. On the other hand, we find in both countries that foreign firms experience positive spillovers from other foreign firms operating in the same product market. This evidence on the dynamics of efficiency is consistent with the view that economies (firms) need to be more technologically advanced and open to competition in order to be able to gain from foreign presence.
Keywords: D20; G32; F23; C33; O33; L20; 330; foreign direct investment; productivity; convergence; frontier; knowledge spillovers; Czech Republic; Russia; Auslandsniederlassung; Direktinvestition; Technische Effizienz; Wissenstransfer; Produktivität; Übergangswirtschaft; Russland; Tschechische Republik